T202. HUMOR-SKILLS TRAINING IN PATIENTS WITH SCHIZOPHRENIA: EFFECTS ON SYMPTOMS AND SOCIAL FUNCTIONING. (1st April 2018) - Falkenberg, Irina; Bitsch, Florian; Berger, Philipp; Nagels, Arne; Straube, Benjamin
Abstract: Background: Humor can provide a method of coping with a variety of stressful situations. Training of humor-related skills has proven effective in clinical samples, although humor training in patients with schizophrenia is relatively rare. Methods: In the present study, patients with schizophrenia have been randomly assigned to either a training of humor abilities or a training of social skills. Training effects on measures of psychopathology, psychosocial functioning and stress were compared between groups. Results: Preliminary analyses revealed that level of negative symptoms, stress and psychosocial dysfunction were significantly reduced in the humor group over the course of the training. Discussion: These results suggest that humor training may improve important clinical and functional outcomes in patients with schizophrenia.